Diversification Strategies of Large Business Groups in the Philippines - Gutierrez, Ben Paul; Rodriguez, Rafael (Philippine Management Review; Vol 20 (2013))
This paper describes the diversification strategies of 11 major Philippine business groups.  First, it reviews the benefits and drawbacks of related and unrelated diversification from the literature.  Then, it describes the forms of diversification being pursued by some of the large Philippine business groups. The paper ends with possible explanations for the patterns of diversification observed in these Philippine business groups and identifies directions for future research.